Rethinking medicalization: discursive positions of children and their caregivers on the diagnosis and treatment of ADHD in Chile - Pablo Reyes; Pablo Cottet; Alvaro Jimenez; Gabriela Jauregui
Abstract The debates around the diagnosis and pharmacological treatment of Attention Deficit and Hyperactivity Disorder (ADHD) have traditionally been approached from the perspective of the "medicalization processes" of children's behaviour. However, this perspective tends to overlook the meanings of diagnosis and treatment of ADHD for children and their caregivers. The purpose of this article is to describe the discursive positions of children and their caregivers on the diagnosis and treatment of ADHD. In-depth interviews were conducted with seven Chilean children and their caregivers. The material was analysed following the procedures of the discourse structure analysis. A discursive structure was identified that configures four emerging realities: the myth of origin of the child's behaviour and learning problems; the ambivalences in/of medicalization; the process of identity (dis)stabilization under diagnosis and treatment; and the subversion of medicalization. It is observed that the subjective experience of the diagnosis and treatment of ADHD is not homogeneous, since different discursive positions, family and institutional understandings that enter into conflict cross it. The experiences of ADHD are shaped by discursive structures that condition the meanings of this experience. The medicalization process is not univocal, but can take different forms and have consequences on children's experiences and social trajectories.